Understanding & Enhancing The Role of IT in The Context of Hotel Global Distribution Systems - Sukhija, Vinod Gurmukh (2008)
The tourism marketplace is a global arena where millions of buyers (travel agents and the consumers) and sellers (hotel accommodations, airline operators, car rentals, tour operators, etc.) work together to exchange travel services. According to preliminary findings presented by the World Tourism Organization (WTO) in January 2007, international tourist arrivals reached an all-time record of 842 million in 2006--an increase of 4.5 percent over 2005. Singapore's Tourism industry has seen a growth of 9% in visitor's arrival in 2006 when compared to 2005. One of the major contributions has been made by online bookings using the Internet. GDS stands for Global Distribution Systems; which are the backbone of major hotel and travel industry's network for web-based bookings. This complex distribution of network is divided among major suppliers and intermediaries. With the help of GDS, buyers and sellers are allowed to make their reservations quickly. This growth in the tourism industry would not have occurred without the GDS infrastructure.